Electrophysiological Signature and the Prediction of Deep Brain Stimulation Withdrawal and Insertion Effects - Trenado, Carlos; Cif, Laura; Pedroarena-Leal, Nicole; Ruge, Diane (Frontiers in Neurology, 2021)
Deep brain stimulation (DBS) serves as a treatment for neurological and psychiatric disorders such as Parkinson’s disease (PD), essential tremor, dystonia, Tourette Syndrome (GTS), Huntington's disease and obsessive compulsive disorder (OCD). There is broad experience with the short-term effects of DBS in individual diseases and their signs/symptoms. However, even in acute treatment and for the same disorder/ or a given disorder, a prediction of effect is not perfect. Even further, factors that influence the long-term effect of DBS and its withdrawal are hardly characterized. In this work, our aim is to share light on an important topic, the question of “DBS dependency”. To address this, we make use of the Kuramoto model of phase synchronization (oscillation feature) endowed with neuroplasticity in order to study the effects of DBS under successive withdrawals and renewals of stimulation neuromodulation as well as influence of treatment duration in de novo DBS “patients”. The results of our simulation show that the characteristics of neuroplasticity have a profound effect on the stability and mutability of oscillation synchronization patterns across successive withdrawal and renewal of DBS in chronic “patients” and also in de novo DBS “patients” with varying duration of treatment (here referred to as “number of iterations”). Importantly, the results demonstrate the strong effect of the individual neuroplasticity makeup on the behavior of synchrony of oscillatory activity that promotes certain disorder/disease states or symptoms. The effect of DBS mediated neuromodulation and withdrawal is highly dependent on the makeup of the neuroplastic signature of a disorder or an individual.